Interactive film scenes for tutor training in problem-based learning (PBL): dealing with difficult situations - Bosse, Hans-Martin; Huwendiek, Sören; Skelin, Silvia Maria; Kirschfink, Michael; Nikendei, Christoph (BMC medical education, 2010)
BACKGROUND: In problem-based learning (PBL), tutors play an essential role in facilitating and efficiently structuring tutorials to enable students to construct individual cognitive networks, and have a significant impact on students' performance in subsequent assessments. The necessity of elaborate training to fulfil this complex role is undeniable. In the plethora of data on PBL however, little attention has been paid to tutor training which promotes competence in the moderation of specific difficult situations commonly encountered in PBL tutorials. METHODS: Major interactive obstacles arising in PBL tutorials were identified from prior publications. Potential solutions were defined by an expert group. Video clips were produced addressing the tutor's role and providing exemplary solutions. These clips were embedded in a PBL tutor-training course at our medical faculty combining PBL self-experience with a non-medical case. Trainees provided pre- and post-intervention self-efficacy ratings regarding their PBL-related knowledge, skills, and attitudes, as well as their acceptance and the feasibility of integrating the video clips into PBL tutor-training (all items: 100 = completely agree, 0 = don't agree at all). RESULTS: An interactive online tool for PBL tutor training was developed comprising 18 video clips highlighting difficult situations in PBL tutorials to encourage trainees to develop and formulate their own intervention strategies. In subsequent sequences, potential interventions are presented for the specific scenario, with a concluding discussion which addresses unresolved issues. The tool was well accepted and considered worth the time spent on it (81.62 +/- 16.91; 62.94 +/- 16.76). Tutors considered the videos to prepare them well to respond to specific challenges in future tutorials (75.98 +/- 19.46). The entire training, which comprised PBL self-experience and video clips as integral elements, improved tutor's self-efficacy with respect to dealing with problematic situations (pre: 36.47 +/- 26.25, post: 66.99 +/- 21.01; p < .0001) and significantly increased appreciation of PBL as a method (pre: 61.33 +/- 24.84, post: 76.20 +/- 20.12; p < .0001). CONCLUSIONS: The interactive tool with instructional video clips is designed to broaden the view of future PBL tutors in terms of recognizing specific obstacles to functional group dynamics and developing individual intervention strategies. We show that this tool is well accepted and can be successfully integrated into PBL tutor-training. Free access is provided to the entire tool at http://www.medizinische-fakultaet-hd.uni-heidelberg.de/fileadmin/PBLTutorTraining/player.swf.
Gesehen am 18.06.2021